2011
DOI: 10.1074/jbc.m111.266536
|View full text |Cite
|
Sign up to set email alerts
|

Revisitation of the βCl-Elimination Reaction of d-Amino Acid Oxidase

Abstract: , which was later confirmed by others (2-4). Based on this, the mechanism depicted in Scheme 1 for the elimination reaction was put forward (1). In this reaction the substrate ␣H as H ϩ is abstracted to form a carbanion intermediate, which then releases Cl Ϫ to yield the final products pyruvate and NH 4 ϩ . In this reaction the redox state of the flavin cofactor remains unaltered."Normal" dehydrogenation of ␤Cl-D-Ala would yield ␤Cl-pyruvate (␤Cl-Py) as the final product and lead to reduction of the flavin cof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This reaction does not in itself constitute an absolute proof. Indeed, it was suggested that halogen elimination could occur after enzyme reduction, when a hydride would displace the halogen from the normal keto acid product, as has been shown for d ‐amino acid oxidase [ 87 ]. However, a number of studies on Fcb2 WT and variant forms provided significant mechanistic information.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction does not in itself constitute an absolute proof. Indeed, it was suggested that halogen elimination could occur after enzyme reduction, when a hydride would displace the halogen from the normal keto acid product, as has been shown for d ‐amino acid oxidase [ 87 ]. However, a number of studies on Fcb2 WT and variant forms provided significant mechanistic information.…”
Section: Discussionmentioning
confidence: 99%
“…N5-adducts have also been proposed in the reaction of monoamine oxidase with several substrates and inhibitors [22]. The β-Cl-elimination activity of D-amino acid oxidase has been proposed to occur via formation of a transient N5-covalent intermediate [23]. In these examples, after the initial attack of the substrate/analogs, formation of a N5-iminium ion or decay of the flavin N5-adduct is coupled to an elimination step (e.g., nitrite, chloride) (Scheme 2).…”
Section: Formation Of Flavin N5-adductsmentioning
confidence: 99%
“…In mammals, it is found in brain, kidneys, liver, lungs, etc. It is remarkable that DAAO concentration in liver and kidneys of pigs is particularly high [7]. Multiple enzyme functions indicate the relation between changes in DAAO activity in the cell with different regulatory processes in the body [8,9].…”
Section: Abstract: D-amino Acids D-amino Acid Oxidase Peroxisomes mentioning
confidence: 99%